Exploration of African natural products as VP35 inhibitors to combat Marburg virus infection: Molecular docking, molecular dynamics, and quantum mechanical computations - Alaa H. M. Abdelrahman; Gamal A. H. Mekhemer; Peter A. Sidhom; Mohamed A. El-Tayeb; Shahzeb Khan; Mahmoud A. A. Ibrahim (PLoS ONE, 2025)
Marburg virus (MBV) is a highly lethal filovirus responsible for hemorrhagic fever with case fatality rates of up to 88%. MBV was first recognized in 1967 during simultaneous outbreaks in Marburg and Frankfurt, Germany, and Belgrade, then part of Yugoslavia (now Serbia), following exposure to infected African green monkeys imported from Uganda. Currently, no approved treatment exists for MBV infection. The viral protein (VP35) plays a critical role in viral replication, transcription, and nucleocapsid assembly, making it a promising antiviral target. Consequently, obstructing the function of VP35 offers a potential strategy for combating MBV. Herein, the African Natural Products (ANP) database, which encompasses over 6,500 compounds, was subjected to virtual screening against VP35 employing docking computations. For inhibitors exhibiting a docking score <−8.0 kcal/mol against VP35, molecular dynamics simulations (MDS) were conducted, along with binding energy assessment utilizing the MM/GBSA approach. Upon the MM/GBSA//250 ns MDS, ANPDB6426, ANPDB5109, and ANPDB6357 demonstrated promising binding affinities toward the VP35, with Δ G binding values of −37.9, −34.6, and −34.2 kcal/mol, respectively. The post-MD analyses demonstrated that all three ANPs remained remarkably stable within the VP35 binding pocket over the full 250 ns MDS. Furthermore, the identified ANPs unveiled favorable oral bioavailability, pharmacokinetic, and safety profiles. Density functional theory calculations further supported the chemical reactivity of the identified ANPs. Compared to galidesivir and favipiravir, reference inhibitors, the estimated MM/GBSA binding energies of the identified ANPs with VP35 were about two times lower than galidesivir and favipiravir. These results highlighted the efficacy of computational methods in recognizing putative VP35 inhibitors, providing promising avenues for additional experimental research and prospective curative advancement toward MBV.